2021
DOI: 10.1097/pai.0000000000000964
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and Role of Mutation-specific H3F3A (Histone 3-3) G34W Immunohistochemistry to Differentiate Giant Cell Tumor of Bone From its Clinicoradiologic and Histologic Mimics: An Institutional Study

Abstract: Giant cell tumor of bone (GCTB) is a benign neoplasm, which can sometimes be a diagnostic challenge, especially in small biopsies, due to its histologic benign and malignant mimics. We evaluated the role of H3.3 G34W immunohistochemistry (IHC) antibody in diagnosing GCTB and its role in differentiating it from its close histologic mimics. A total of 120 cases (80 cases of GCTB and 40 cases of histologic mimics) were retrieved and subjected to IHC. Of 80 cases of GCTB, 72 cases showed a positive nuclear immunoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Several recent studies have demonstrated that the H3F3A mutation might contribute to distinguishing GCTB-related tumors from those that are giant-cell-rich [ 10 , 52 , 53 , 54 ]. However, there are differences in the frequency of H3F3A mutations found in previous reports; these mutations were identified in 69–100% of GCTB [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. One study [ 54 ] suggested that diagnosis of GCTB without the H3F3A alteration should be confirmed with considerable caution.…”
Section: Discussionmentioning
confidence: 85%
“…Several recent studies have demonstrated that the H3F3A mutation might contribute to distinguishing GCTB-related tumors from those that are giant-cell-rich [ 10 , 52 , 53 , 54 ]. However, there are differences in the frequency of H3F3A mutations found in previous reports; these mutations were identified in 69–100% of GCTB [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. One study [ 54 ] suggested that diagnosis of GCTB without the H3F3A alteration should be confirmed with considerable caution.…”
Section: Discussionmentioning
confidence: 85%
“…The expression of H3.3 G34W mutant protein in GCTB after denosumab therapy suggests that tumor stromal cells may play a role in the formation of a new bone. Therefore, the detection of H3F3A by IHC or sequencing is extremely helpful for the diagnosis of bone tumors lacking giant cells [ 45 , 46 , 47 ]. Some scholars have compared the sensitivity and specificity of sequencing and IHC for detecting the H3F3A gene for GCTB diagnosis.…”
Section: The Influence Of Dose and Duration Of Denosumab Therapy On G...mentioning
confidence: 99%